Teachers’ Satisfaction: Implications for Job Performance (Interdisciplinary Research in Education, 2021)
The main objective of this study is to explore the teachers' satisfaction and their implications on job performance in schools. This study is based on a qualitative phenomenological research design and the study focused on perspectives of teachers' job satisfaction. Secondary data analysis is used and analyzed qualitatively with critical review. In educational sector, teachers are the individuals, who deliver an effective contribution in imparting knowledge, attitudes, development of skills and abilities, leading to overall growth and development of the students and welfare of the community. They are professional and ethical in their job performance. It is vital for the teachers to be satisfied with their job in order to perform their duties up to the required standard. Results show that a lack of resources, lack of dynamic leadership, overcrowded classes, lacks of discipline among learners, work overload, low salary, administrative issues, and lack of recognition by principals, job security, lack of professional opportunities, and parents for good work done were serious sources of dissatisfaction among teachers. The findings, implications from this study include offering specific professional development suggestions, as well as critical way for further examining teachers’ motivation to learn as a research topic and theoretical construct.